2020
DOI: 10.1021/acs.jpcb.0c03357
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Dynamics in Ionic Liquids: A Combined NMR and MD Simulation Study

Abstract: The translational dynamics of xenon gas dissolved in room-temperature ionic liquids (RTILs) is revealed by 129 Xe NMR and molecular dynamics (MD) simulations. The dynamic behavior of xenon gas loaded in 1-alkyl-3-methylimidazolium chloride, [C n C 1 im]Cl ( n = 6, 8, 10), and hexafluorophosphate, [C n C 1 im][PF 6 ] ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…[ 144,145 ] The group also assessed the diffusion of xenon in different IL in order to better understand separation processes in IL phases. [ 146 ] Heinze et al also used 129 Xe NMR along with nitrogen physisorption to evaluate the behavior of IL in porous silica supports such as SBA‐15 and MCM‐41. Particular emphasis was placed on studying the formation of isolated droplets versus layers.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…[ 144,145 ] The group also assessed the diffusion of xenon in different IL in order to better understand separation processes in IL phases. [ 146 ] Heinze et al also used 129 Xe NMR along with nitrogen physisorption to evaluate the behavior of IL in porous silica supports such as SBA‐15 and MCM‐41. Particular emphasis was placed on studying the formation of isolated droplets versus layers.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…Therefore, the possibility or xenon to explore both kind of environments, in TFSI salts, makes it more sensitive the overall dynamics of the hosting matrix, and the trend in the diffusion coefficient is indeed in agreement with the increasing viscosity as the chain length is increased. In contrast, when the environment explored by xenon as limited to the alkyl domain, as in [C n C 1 im][Cl], xenon diffusion is not only independent of the increasing viscosity of the matrix but it shows an opposite behaviour thanks to the increasing size and interconnection of the non-polar domains, as was discussed in Ref [53]. Finally, it is interesting to compare the observed trends for all the experimental NMR parameters: diffusion, relaxation and chemical shift.…”
Section: Discussionmentioning
confidence: 99%
“…work [53] we compared the interaction energy between a xenon atom and the imidazolium alkyl chain, and we found that the FF was in excellent agreement, concerning contact distance and well depth, with the dispersion corrected M06-2X level. Initial boxes were prepared with packmol [74] and contained 400 ion pairs and one xenon atom.…”
Section: Simulationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Since the interpretation of such spectral features is often nontrivial and may lead to contradicting viewpoints, it can be augmented by molecular dynamics (MD) simulations which serve as a mathematical microscope into the atomistic world. 4 6 …”
mentioning
confidence: 99%